Modernization of Islamic education and Islamic thought in Indonesia - Abidin, Zainal; Ahyar, Saiful; Wardah, Wardah (Edumaspul: Jurnal Pendidikan, 2022)
An article that departs from ideas in analyzing modernization in the context of education, especially in Islamic education in Indonesia. This research was assisted by library research methods (library research). In obtaining research data, researchers collect, analyze, and organize, sources from articles. The research results show that Islamic philosophy developed until new religious concepts emerged in the Muslim world. Because of how these ideas developed, it is clear how the social, political, and cultural life of Muslims was significantly influenced by their movement patterns and world views. Religious education and beliefs influence the way people act and think. The Syafi'i school of thought dominates the religious worldview of Muslims who are developing in Indonesia. Indonesian Muslims in general still adhere to the texts of the mujtahid school of thought (the quality school), and they have not received methodological education (the school), which means they advocate law according to the mujtahid mindset, which has been produced by the school's imam.